Spark Plasma Sintering of Aluminum-Magnesium-Matrix Composites with Boron Carbide and Tungsten Nano-powder Inclusions: Modeling and Experimentation - Dvilis E. S. Edgar Sergeevich; Khasanov O. L. Oleg Leonidovich; Gulbin V. N. Viktor Nikolaevich; Petyukevich M. S. Mariya Stanislavovna; Khasanov A. O. Aleksey Olegovich; Olevsky E. A. Evgeny Aleksandrovich (2016, 2016)
Title screen